2013
DOI: 10.1155/2013/940106
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Peritoneal Dialysis Catheter Implantation Technique by Nephrologists

Abstract: Peritoneal dialysis catheter (PDC) is the lifeline of peritoneal dialysis (PD) patients. One of the critical issues for successful PD is a well-functioning PDC which is timely inserted. It is the implantation technique rather than the catheter design that determines the outcome of the catheter. Dedication in acquiring the appropriate technique is vital to the success of a PD program. In this paper, we discuss the pros and cons of various techniques used for PDC implantation. A detailed description of PDC impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Compared to open surgery, laparoscopy provides the ability to directly visualize the placement of catheter tip in pelvis and proactively address anatomic problems that might result in mechanical dysfunction . Therefore, it is increasingly being used in the establishment of peritoneal access.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to open surgery, laparoscopy provides the ability to directly visualize the placement of catheter tip in pelvis and proactively address anatomic problems that might result in mechanical dysfunction . Therefore, it is increasingly being used in the establishment of peritoneal access.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to open surgery, laparoscopy provides the ability to directly visualize the placement of catheter tip in pelvis and proactively address anatomic problems that might result in mechanical dysfunction. 16 Therefore, it is increasingly being used in the establishment of peritoneal access. It is reported that the laparoscopic PD catheter insertion technique had a higher one year catheter survival rate and the incidence of catheter migration is lower.…”
Section: Discussionmentioning
confidence: 99%
“…For such high-risk patients, low-risk surgery is required under local anesthesia instead of general anesthesia. Recently, the cases in which nephrologists have inserted PDC are increasing and good outcomes have been reported worldwide in these cases (7)(8)(9). However, nephrologists who are not surgeons should not perform high-risk operations.…”
Section: Discussionmentioning
confidence: 99%
“…PD compared to hemodialysis has the advantages of a better quality of life, simplicity in use, no need for vascular access and an almost similar outcome in the first year of dialysis (1,3). PD-related complications, such as catheter obstruction, displacement, pericanular leakage, peritonitis, and outlet infection, may lead to loss of the catheter and the need to change from PD to hemodialysis, which can be uncomfortable and expensive for the patient (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The later has gain popularity in recent years. Most previous studies comparing these two approaches were conducted in adult patients (6)(7)(8)(9)(10), and studies comparing the outcome in children are few in the literature (11). Therefore, the present study aims to compare these two approaches for PD catheter insertion is in children under the age of seven years.…”
Section: Introductionmentioning
confidence: 99%